The role of stem cells in cystic fibrosis disease modeling and drug discovery. (2nd December 2018) - Conese, Massimo; Beccia, Elisa; Carbone, Annalucia; Castellani, Stefano; Di Gioia, Sante; Corti, Fabiola; Angiolillo, Antonella; Colombo, Carla
ABSTRACT: Introduction : Cystic fibrosis (CF) is the most fatal autosomal recessive disorder caused by the absence/dysfunction of the CF transmembrane conductance regulator ( CFTR ) protein at the apical membrane of epithelial cells. The variety of innovative drug- and gene-based approaches warrants the development of assays that can allow disease modeling and high-throughput screening of drugs. Areas covered : This article aims to highlight the role of stem cells in the development of models that can recapitulate the pathophysiology of CF in the lungs, pancreas, liver, and gut. Particular emphasis will be placed upon the use of these models, derived from induced pluripotent stem cells (iPSCs) and adult stem cells, in the screening of innovative drugs that are in the development pipeline. Expert opinion : iPSCs and adult stem cells have allowed the reconstitution of facets of CF disease in vitro and in vivo models, and, when converted to organoids, have been successfully employed for the screening of drug and gene therapies across CF patients with both common and rare CFTR mutations. These systems can be further optimized for establishing a correlation between ex-vivo effects and in vivo responses in patients and offer an unprecedented opportunity to realize a personalized approach to the treatment of CF.